PELAKSANAAN MC DAN KEPROTOKOLAN DALAM MENGEMBANGKAN KEMAMPUAN BERKOMUNIKASI - Dina Alamianti; Dudi Yudhakusuma; Lusy Mukhlisiana (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
The impact of commnunication technology on social life for millennials in the digital era today, millennials will choose to be communicate with writing rather than oral communication. Communicaion with writing can be one of the inhibiting factors for communication formal and informal ways. In fact, the key for self success is being able to be a good speaker and not talking only. The roles of MC and Protocol is to provide understanding and awareness about public speaking and through MC and protocol activities and can make someone especially students to be a good person and useful for community. In the end, the methods of communication for students are like lecturing about MC and protocol, question and answer also using simulation.